Efektifitas Model Group Investigation dalam Meningkatkan Hasil Belajar IPS Di Sekolah Dasar - Basirun Basirun; Tarto Tarto (UM Purwokerto Press, 2022)
Learning in the 21st century directs students to formulate problems and suppress cooperation in groups to be able to think critically and communicatively. Students at this time are expected to be able to investigate a topic by learning discovery, learning content and learning to work cooperatively so that learning objectives are achieved. The purpose of this study was to determine the effectiveness of the Model Group Investigation on improving social studies learning outcomes in elementary schools. The problem-solving effort above is that the teacher must use an appropriate learning model so that students increase their learning outcomes. Group Investigation (GI) is a complex cooperative learning model because it combines the principles of cooperative learning with constructivism-based learning. The essence of the Group Investigation (GI) learning model is that when the teacher's learning process involves small groups where students work using cooperative inquiry. The advantage of using the Group Investigation (GI) type cooperative model is that students work together and interact with each other so as to make students more active in the learning process from the beginning to the end of learning. The methodology used in this research is a qualitative research that is library research that uses journals, books and other literatures as objects of study. This research produces information in the form of notes and descriptive data contained in the text under study. This qualitative research uses descriptive analysis. The descriptive analysis method will provide a clear, objective, systematic, analytical and critical description of the effectiveness of the Group Investigation (GI) model in improving social studies learning outcomes in elementary schools. The results of this study conclude that the Group Investigation (GI) model can improve social studies learning outcomes in elementary schools.